2012
DOI: 10.1111/1475-6773.12008
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Price Indexes for Patients with Employer‐Provided Insurance: Nationally Representative Estimates from MarketScan Data

Abstract: Our findings suggest that the health component of inflation may be overstated by 0.7 percentage points per year, and real GDP growth may be understated by a similar amount. However, more work may be necessary to precisely replicate the indexes of the BLS to obtain a more accurate measure of these price differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…First, for nearly every disease category, there is a shift away from spending on inpatient services. This is consistent with the results of Aizcorbe and Nestoriak () and Dunn et al, , who showed that substitution away from inpatient services generally leads to a lower MCE relative to an SPI. This savings from reduced utilization on inpatient services is partly offset by a strong increase in the utilization of physician services for most disease categories.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…First, for nearly every disease category, there is a shift away from spending on inpatient services. This is consistent with the results of Aizcorbe and Nestoriak () and Dunn et al, , who showed that substitution away from inpatient services generally leads to a lower MCE relative to an SPI. This savings from reduced utilization on inpatient services is partly offset by a strong increase in the utilization of physician services for most disease categories.…”
Section: Resultssupporting
confidence: 92%
“…In particular, they found that the SPI‐encounter measure grows faster than an episode‐based MCE measure, implying that the SPI‐encounter measure would overstate inflation in the health sector. This result appears to be quite robust and has been replicated in other studies, including those by Dunn et al and Aizcorbe et al . Overall, this research hints that official price indexes may not be an accurate measure for tracking the cost of disease treatment.…”
Section: Introductionsupporting
confidence: 77%
“…First, MarketScan Commercial data are a convenience sample of the US population with ESI that over-represents states in the South and underrepresents states in the West, which have the highest expenditures. 25 The average expenditures for preterm infants in the South were 12% less than the sample mean, and in the West they were 32% greater than the sample mean. Therefore, the unweighted expenditures likely underestimate expenditures for US ESI plans.…”
Section: Discussionmentioning
confidence: 91%
“…Both samples have a high proportion of PPO plans accounting for about two thirds of all observations. 22 We removed outliers we believe are attributable to clerical data input error by discarding episodes in the bottom first percentile and top 99th percentile based on price per service and utilization. 23 An important benefit of the SK&A data relative to other data sources is that they provide information about physician medical practice groups (i.e., firms).…”
Section: Creating a Measure Of Service Pricesmentioning
confidence: 99%